Justice Without Limits: A Philosophical and Ethical Perspective on International Criminal Agreements - Indaryanto, Nanung Nugroho; Widiastuti, Arum (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Justice in international criminal agreements requires deep philosophical and ethical considerations, because international criminal agreements often relate to universal humanitarian aspects and cross-border human rights. Philosophical and ethical perspectives are expected to provide justice that applies without geographical and political limitations. International criminal treaties that seek to achieve unlimited justice must take into account various philosophical and ethical views to create a strong foundation. In the increasingly complex movement of global society, a universal and comprehensive approach to justice is very important, because global solidarity is needed in overcoming crimes that violate humanity, as well as emphasizing the importance of moral integrity in carrying out justice at the international level.